Searching for Brunanburh: The Yorkshire Context of the 'Great War' of 937. (1st August 2013) - Wood, Michael
Abstract : The site of the Battle of Brunanburh has long been controversial, but a consensus has grown over the last few years that it should be located in the Wirral. This article sets out to show that the events of the war of 937 must be understood in the context of Northumbrian history in the Viking age, and that the battle probably took place south of York in the main war zone of the second quarter of the tenth century. A new location is proposed near the River Went, whose name it is suggested is contained in an alternative Northumbrian name for the battle, Wendun.